Kansans in the Middle of the Pandemic: Risk Perception, Knowledge, Compliance with Preventive Measures, and Primary Sources of Information about COVID-19 - Geana, Mugur (Kansas Journal of Medicine, 2020)
Introduction. As we conduct this study, the world is in the grasp of a deadly pandemic. In less than six months since its first diagnosis in Wuhan, China, the COVID-19 infectious disease due to the novel coronavirus has infected over 5,000,000 people and claimed over 350,000 lives. In the United States, most of the cases are in large urban settings along the coasts, but the disease is slowly progressing through the mainland. Kansas, with its particular location in the midwest United States, has seen a relatively small number of cases, but these are increasing. The Kansas government took radical measures to prevent the spread of the disease. According to the Health Beliefs Model, an individual’s perception of risk will dictate engagement with preventive behaviors. Knowledge about the disease and preventive measures drive the risk assessment. Knowledge is dependant on the sources of information used. This study explored these metrics in a sample of Kansans living in the times of the COVID-19 pandemic.Methods. A combination of snowball samples and random distribution through social media was used to recruit participants to an online survey. The risk and knowledge instrument was developed and validated by WHO Europe. Data collection lasted 96 hours.Results. The attitudes and behaviors of Kansans concerning COVID-19 were consistent with its location in an area of the country with a relatively lower incidence of the disease. Participants had good knowledge about the disease and preventive measures and were willing to comply with recommendations from local authorities.Conclusion. Localized information sources that cater to the community are often primary, while social media is not a valuable source for information pertinent to COVID-19.